1996
DOI: 10.1002/hep.510230532
|View full text |Cite
|
Sign up to set email alerts
|

Is the Mayo model for predicting survival useful after the introduction of ursodeoxycholic acid treatment for primary biliary cirrhosis?

Abstract: Treatment of patients with primary biliary cirrhosis eral prognostic indicators have been proposed and (PBC) using ursodeoxycholic acid (UDCA) leads to a re-prognostic indexes developed to predict survival. duction in serum bilirubin. The first objective of this Shapiro et al. 1 showed that serum bilirubin is a good study was to assess the performance of certain prognos-predictor of survival in PBC, and elevated serum bilirutic indicators for PBC after the introduction of treat-bin levels have been used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
1
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
2
34
1
2
Order By: Relevance
“…10 UDCA has also been shown to decrease both the risk of developing esophageal varices 11 and the Mayo risk score, a cross-validated index of survival in PBC. [12][13][14] The effects of UDCA on liver histology are less clear. Using different histological scoring systems, improvement in some histological features such as piecemeal necrosis, 3,8 inflammation, 3,8,15 cholestasis, 3,8 bile duct paucity, and proliferation 3,7,16 have previously been reported in randomized, placebo-controlled trials.…”
mentioning
confidence: 99%
“…10 UDCA has also been shown to decrease both the risk of developing esophageal varices 11 and the Mayo risk score, a cross-validated index of survival in PBC. [12][13][14] The effects of UDCA on liver histology are less clear. Using different histological scoring systems, improvement in some histological features such as piecemeal necrosis, 3,8 inflammation, 3,8,15 cholestasis, 3,8 bile duct paucity, and proliferation 3,7,16 have previously been reported in randomized, placebo-controlled trials.…”
mentioning
confidence: 99%
“…In addition, although the effect of silymarin on survival or development of liver-related complications was not the primary end-point of the current study, the Mayo risk score, a cross-validated index of survival in PBC, 11,23,29,32 was not improved; indeed, it increased at the end of the treatment period, further reflecting the lack of a significant effect of silymarin on clinically relevant outcomes. The combination of UDCA and colchicine has shown to be of no benefit for suboptimal responders to UDCA alone in a large, controlled trial.…”
Section: Discussionmentioning
confidence: 67%
“…Serum bilirubin levels, a useful prognostic marker in treated 29,30 and untreated [23][24][25][26][27][28]31 patients with PBC, were not affected by the combination of UDCA and silymarin, and none of our patients showed a complete normalization of liver biochemistries during combination therapy. In addition, although the effect of silymarin on survival or development of liver-related complications was not the primary end-point of the current study, the Mayo risk score, a cross-validated index of survival in PBC, 11,23,29,32 was not improved; indeed, it increased at the end of the treatment period, further reflecting the lack of a significant effect of silymarin on clinically relevant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of the clinical and biochemical measures used for comparison in this study have previously been shown to be of prognostic value in predicting outcome after liver transplantation. [9][10][11][12]18 There was no difference between UDCA and placebo groups when all pretransplantation prognostic factors were compared, which would suggest that UDCA-treated patients with PBC should have a similar posttransplantation outcome to untreated patients. There was no difference between UDCA and placebo groups with respect to 1-month and 1-year posttransplantation survival and infection.…”
Section: Discussionmentioning
confidence: 99%